Staphylococcus aureus infection risk in a population of health sciences students at a public university - Mat Azis, Norhidayah; Ab Hamid, Amielia; Pung, Hui Ping; Abdul Rafee, Putri 'Amirah; Yahya, Farizatul Akmawati; Amin Nordin, Syafinaz; Neela, Vasantha Kumari; Suhaili, Zarizal; Mohd Desa, Mohd Nasir (Tehran University of Medical Sciences, 2014)
Background: This study was undertaken to evaluate Staphylococcus aureus carriage and persistence in health sciences students at the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia.